The Analysis of EUR/USD Exchange Rate - Fistein, Benjamin (2013)
Exchange rates are among the most closely scrutinized macroeconomic indicators in today's global economic environment. The EUR/USD exchange rate is particularly significant, as it represents the two most powerful economic entities and most frequently held foreign reserve currencies. This thesis focuses on the driving forces behind the development of the euro-dollar rate over the past decade and attempts to analyze which determinants had the most significant impact over this time period. Each determinant will be examined by contrasting the indicator's differential between the U.S. and the eurozone with the percentage change of the EUR/USD exchange rate. Those determinants whose impact could not have been analyzed in this paper became the subject of personal interviews with leading Czech economists. The results surprisingly point to a relatively small correlation between GDP growth rate differences and the exchange rate, while the unemployment and inflation differentials appeared to correlate more closely with EUR/USD fluctuations. The analysis and interviews also lead to the conclusion that U.S. monetary policy significantly contributed to the development of this particular exchange rate.